Effectiveness of Vitamin C Administration on Outcome in COVID-19 Patients: A Systematic Review and Meta-Analysis - Desie Dwi Wisudanti; Nur Lintang Nabilah Sri Kusumasari; Adelia Handoko; Cholis Abrori; Angga Mardro Raharjo (Jurnal Respirologi Indonesia, 2023)
Background: Numerous studies on the effectiveness of vitamin C against the COVID-19 infection have been widely carried out recently. However, the differences in dosage ranges and therapeutic efficacy in previous studies have prompted a systematic literature review on the effectiveness of vitamin C on outcomes in COVID-19 patients. In addition, this study aimed to determine the appropriate therapeutic dose of vitamin C for COVID-19 patients, either alone or in combination with other supplements, and to determine the side effects.Methods: Gleaned from the search on Pubmed, Science Direct, and Google Scholar databases up to April 25, 2022, fourteen studies were relevant, namely five studies using vitamin C orally and nine studies administered intravenously. We assessed multiple outcomes, including mortality, hospitalization, and symptoms. The quality and risk of bias analyses were performed using JBI critical appraisal tools.Results: The oral administration of vitamin C resulted in a significant difference in the mortality of COVID-19 patients (OR=0.66; 95% CI=0.45–0.97; P=0.04; I2=0%) and a non-significant difference in the outcome. Duration of hospitalization (OR = -0.21; 95% CI = -2.70-2.28; P=0.87; I2=94%). Regarding the cost-effectiveness and side effects manifested in digestive disorders such as nausea, diarrhea, stomach cramps, and vomiting, vitamin C with a dose of 500-1000 mg could be given orally.Conclusion: Oral administration of vitamin C showed a reduction in the mortality of asymptomatic COVID-19 patients with moderate symptoms.